The Potential Properties of Natural Compounds in Cardiac Stem Cell Activation: Their Role in Myocardial Regeneration - Carresi, Cristina (Nutrients, 2021)
Cardiovascular diseases (CVDs), which include congenital heart disease, rhythm disorders, subclinical atherosclerosis, coronary heart disease, and many other cardiac disorders, cause about 30% of deaths globally; representing one of the main health problems worldwide. Among CVDs, ischemic heart diseases (IHDs) are one of the major causes of morbidity and mortality in the world. The onset of IHDs is essentially due to an unbalance between the metabolic demands of the myocardium and its supply of oxygen and nutrients, coupled with a low regenerative capacity of the heart, which leads to great cardiomyocyte (CM) loss; promoting heart failure (HF) and myocardial infarction (MI). To date, the first strategy recommended to avoid IHDs is prevention in order to reduce the underlying risk factors. In the management of IHDs, traditional therapeutic options are widely used to improve symptoms, attenuate adverse cardiac remodeling, and reduce early mortality rate. However, there are no available treatments that aim to improve cardiac performance by replacing the irreversible damaged cardiomyocytes (CMs). Currently, heart transplantation is the only treatment being carried out for irreversibly damaged CMs. Hence, the discovery of new therapeutic options seems to be necessary. Interestingly, recent experimental evidence suggests that regenerative stem cell medicine could be a useful therapeutic approach to counteract cardiac damage and promote tissue regeneration. To this end, researchers are tasked with answering one main question: how can myocardial regeneration be stimulated? In this regard, natural compounds from plant extracts seem to play a particularly promising role. The present review will summarize the recent advances in our knowledge of stem cell therapy in the management of CVDs; focusing on the main properties and potential mechanisms of natural compounds in stimulating and activating stem cells for myocardial regeneration.